Art on the scale of life - Böhm, Kathrin 1969- (Sternberg Press, 2023)
This volume critically profiles, contextualizes, and theoretically elaborates the unique practice of the UK-based German artist Kathrin Böhm. Combining visual and textual material, it offers an overview of Böhm's exceptional modus operandi that is rooted in a highly original artistic synthesis of a range of practices. Over the last three decades, Böhm has expanded the terms of socially engaged ways of working to an unprecedented scale and breadth by producing complex organizational, spatial, visual, and economic forms. These often entail the production of complex infrastructures, manifested via projects such as Culture is a Verb (2018–21), The Centre for Plausible Economies (2018–ongoing), Company: Movements, Deals and Drinks (2014–ongoing) and the Eco-Nomadic School (2010–ongoing). The book follows a major mid-career exhibition at The Showroom, London, in 2021. Offering a significant addition to debates on contemporary art and architecture, social action, and public culture, Kathrin Böhm: Art on the Scale of Life brings together critical reflections by internationally acclaimed contributors. Spanning a wide range of critical positions and disciplines, these include Dave Beech, Céline Condorelli, Elvira Dyangani Ose, Wapke Feenstra, Katherine Gibson, Joon-Lynn Goh, Lily Hall, Yolande Zola Zoli van der Heide, Grace Ndiritu, Gerrie van Noord, Paul O’Neill, Doina Petrescu, Gregory Sholette and THEMM!!, Kuba Szreder, Gavin Wade, Mick Wilson, Stephen Wright, and Franciska Zólyom. In addition, material derived from Böhm's international networks and projects provides an in-depth impression of the deeply ingrained collaborative and durational nature of her way of working. Photographic, diagrammatic, and typographical imagery runs through the book, demonstrating the rich visual and spatial languages embedded in Böhm's work
Zusatz auf Umschlag: "Made by many"
Keywords: Böhm, Kathrin -- 1969-